IMPLEMENTASI PETA PIKIRAN (MIND MAP) DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA SMP DI KOTA SEMARANG - Tjahyono, Heri; Aji, Candra Purnama (Universitas Negeri Semarang, 2010)
The 2006 curriculum known as KTSP demands the change of paradigm in theworld of teaching and learning including in learning social science. Some teachingand learning activities done by the teachers are still using the lecturing method whichpositioning the teachers as the centre of information. Therefore, as the writers of thisresearch, we try to apply a learning method by using in order to stimulate thestudents' activities and critical thinking. This research was aimed to find out whetherthere was a significant difference in the result of social science learning of junior highschool students which was done through lecturing method and mind map, especiallytoward certain material such as The research method conducted for thispurpose was an experiment using research designThe variables consisted of independent variable (i.e. theimplementation of mind map method toward learning process about ),and dependent variable (i.e. students' activities and test result). The population for thisresearch was the VIII (eighth) grade students of State Junior High School 30,Semarang.As the sample of research, we chose two classes randomly. One was taughtby using a mind map method treatment and another, control class, by using variedlecturing method. The result of this research showed that the learning result oftreatment/experiment class was 76.67 in average, with the highest score 90.00 and thelowest 60.00. This was significantly different from the control class which scored72.83 in average, with the highest score 86.67 and the lowest 60.00. Thus, the result ofthe experiment classwas better than the control class.Kata kunci: Mind map,KTSP, pembelajaran IPS